LITHOLOGIC AND GEOPHYSICAL PROPERTIES OF SHALE WITH A HIGH CONTENT OF KEROGEN - Karpenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The key features of unconventional shale hydrocarbon accumulations include the following: a) all source rocks act as low permeability oil and gas reservoir rocks requiring no cover rock; b) effective pore space is distributed within the bulk of mature kerogen resulting from katagenetic transformations in organic material. Evaluating the properties of reservoir rocks with a high content of kerogen attracts a lot of interest due to new approaches to unconventional hydrocarbon exploration and the challenge of applying the technology of hydraulic fracturing in low-permeability formations. This research into the lithological and physical properties of facies with a high kerogen content was prompted by a correlation between the sedimentary features of the proven productive shale formations and similar formations of different ages in the Dnieper-Donets basin. The sedimentary conditions of shale formation in DDb being similar to those of forming oil and gas producing shales with a high content of kerogen in Utica/Point Pleasant paleobasins, the highest kerogen content was assumed to be associated with certain lithotypes holding interest for further study. Mathematical equations were derived to describe the correlation between radioactivity, uranium content, bulk density, electrical resistivity and organic carbon content for shales from the Utica formation and the DDb shales. There were clarified mathematical dependences of bulk density on organic carbon content for a number of Lower Carboniferous formations in DDb. As using separate mathematical expressions is likely to produce results of doubtful validity, preference should be given to a system of equations to describe the nature of changes in different physical properties of shales depending on the organic component content. That will provide accurate data on the share of kerogen in the studied reservoir rocks. Values of hydrogen and oxygen indices only predict low molecular weight products and their subsequent extraction. The findings on the lithological properties and mathematical relationships have been reported and discussed at international conferences.
Keywords: hydrocarbons; kerogen; organic carbon content; shale; sonic log; radioactivity; resistivity log; bulk density log; component composition